2016
DOI: 10.1161/strokeaha.116.013760
|View full text |Cite
|
Sign up to set email alerts
|

Antiphospholipid Antibodies and the Risk of Stroke in Urban and Rural Tanzania

Abstract: Background and Purpose-The burden of stroke is high in sub-Saharan Africa, and improved knowledge of risk factors is needed. Antiphospholipid antibodies are a common acquired stroke risk factor in young individuals. Antiphospholipid antibodies may be induced by infectious diseases. Sub-Saharan Africa has a high infectious burden, and we analyzed the contribution of antiphospholipid antibodies to the risk of stroke in an incident population from rural and urban Tanzania. Methods-Stroke cases and age-and sex-mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…A case-control study of stroke conducted in Tanzania between 2003–2006 enrolled 158 stroke cases and 369 age- and sex- matched controls[ 42 ]. Serology for syphilis was performed using an IgG ELISA ( Treponema pallidum IgG ELISA; IBL international GmbH, Hamburg, Germany).…”
Section: Resultsmentioning
confidence: 99%
“…A case-control study of stroke conducted in Tanzania between 2003–2006 enrolled 158 stroke cases and 369 age- and sex- matched controls[ 42 ]. Serology for syphilis was performed using an IgG ELISA ( Treponema pallidum IgG ELISA; IBL international GmbH, Hamburg, Germany).…”
Section: Resultsmentioning
confidence: 99%
“…Data from 158 stroke cases and 369 controls indicated that LAC is a strong risk factor for stroke, especially in young and middle-aged individuals. On the contrary, the presence of other aPLs showed very low association with increased risk for stroke 16 .…”
Section: Introductionmentioning
confidence: 86%
“…62 Data obtained from large population-based case-control studies and prospective cohort studies among aPL carriers support the prothrombotic properties of isolated LA. 3,17,34,61 Prospective data indicate that thrombotic complications occur three-to fourfold more often in these patients than is expected in people of the same age. 3,61 The Lupus Anticoagulant Paradox…”
Section: β2gpi-dependent Versus β2gpi-independent Lupus Anticoagulantsmentioning
confidence: 92%
“…27 The association between antiprothrombin antibodies and thrombosis is currently unclear: Several studies report an association with thrombosis, [28][29][30][31][32] which is contradicted by others. 17,28,33,34 There are several possible reasons for this discrepancy, including differences in study design, patient population, control group, and method used to detect the antiprothrombin antibodies (and thus, probable heterogeneity in antiprothrombin antibodies themselves). While some studies focused on venous thromboembolism, others investigated arterial thrombosis, which likely represent two different pathophysiologic mechanisms, with differences in the involved cell type, fluid shear stress, and the contribution of the coagulation system to thrombus formation.…”
Section: Antibodies Against Prothrombin Cause Lupus Anticoagulantmentioning
confidence: 99%